The role of the United Nations in protecting the rights of refugee children (An analytical study) - Al-Qahtani, Sarah Mohammed; Al-Makki, Rawa Ghazi (Journal of Humanities & Social Sciences, 2023)
International law aims to ensure the protection and maintenance of the rights of refugee children, and to realize this goal, the law has set a set of rules and agreements that seek to dedicate the actual, realistic and legal protection to this protection. It is noted that this law has guaranteed special protection for the groups of people most effected and affected by what may result from asylum, including a group of refugees. Children are the most vulnerable group of refugees. In view of the recognized special weakness of the child in order to achieve the comprehensiveness of the legal framework for his protection, international law established a set of agreements on asylum, which in turn provided for a set of mechanisms and devices that contribute and assist refugees in general and children in particular by dedicating and enjoying their rights in most of countries they have sought refuge.